AN INVESTIGATION INTO THE PHENOMENON OF GLOSSINESS IN CONTEMPORARY ARCHITECTURE - Badruddin, Atthaillah (Arsitekno, 2013)
This paper will investigate the phenomenon of glossiness as a rising trend in contemporary architecture. Also,this paper will argue a significant transition in the surface finishing and socio-technical development hasdirected architecture toward the trend of glossiness. To gain a better understanding toward this particularphenomenon, the exploration within this study will be discussed in two parts. First, we will look at glossiness asmaterial quality and the limitation of perception. This will suggest the glossiness as a result of the interactionbetween the known material qualities, such as transparency, reflectivity and opacity. Next, we will further lookat this particular phenomenon in socio-technical development in the 20th century to understand why theglossiness has present in the contemporary architecture. Consequently, this understanding will bring us to thecomprehension of glossiness as a product of consumerism culture and computer innovation in architecturesurface materiality.